1D/2D Rod-sheet Shape Bi2S3 Photocatalyst for Photocatalytic Reduction Cr(VI) under Visible Light - Wu, Xinzhuo; Chen, Shaojie; Jiang, Yinxing; Zhao, Xinshan; Li, Zhao; Zhou, Yingmei; Li, Jing (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
The crystal structure and morphology of photocatalysts play a crucial role in determining their photocatalytic performance. In this study, we synthesized and investigated 1D/2D Bi2S3 as a potential visible-light-activated photocatalyst for the reduction of aqueous Cr(VI). The 1D/2D Bi2S3 was synthesized using hydrothermal synthesis technique by heating Bi2(H2O)2(SO4)2(OH)2 precursor and sodium sulfide at 190 ℃ for 24 h, where the molar ratio of Bi to S elements in the reaction reagents was changed from 1:6 to 2:3. The structure, composition, and optoelectronic properties of the prepared Bi2S3 were characterized using X-ray diffraction, UV-vis diffuse reflectance spectra, field emission scanning electron microscopy, electrochemical impedance spectra, and transient photocurrent. It is shown that the prepared orthorhombic Bi2S3 has full-spectrum photoresponsivity. Bi2S3-B with 1D/2D heterogeneous structure exhibits the lowest charge carrier transport resistance, and its photocurrent intensity is nearly twice that of Bi2S3-C. It demonstrates the highest photocatalytic activity in visible-light photocatalytic reduction of aqueous Cr(VI), with a reduction rate of 54.5% after 140 minutes of light exposure. According to the bandgap of Bi2S3 and radical scavenger experiments, a reaction mechanism for the photocatalytic reduction of Cr(VI) by Bi2S3 was proposed. Furthermore, the results highlight the economic and environmentally friendly nature of the hydrothermal synthesis method using homemade precursors, which allows for the regulation of Bi2S3 morphology and the enhancement of its visible photocatalytic activity. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).